Emodin Attenuates Lipopolysaccharide-Induced Acute Liver Injury via Inhibiting the TLR4 Signaling Pathway in vitro and in vivo - Ding, Yan; Liu, Pan; Chen, Zhi-Lin; Zhang, Shao-Jun; Wang, You-Qin; Cai, Xin; Luo, Lei; Zhou, Xuan; Zhao, Lei (Frontiers in Pharmacology, 2018)
Aims: Emodin is an anthraquinone with potential anti-inflammatory properties. However, the possible molecular mechanisms and protective effects of emodin are not clear. The objective of this study was to investigate the possible molecular mechanisms and protective effects of emodin on lipopolysaccharide (LPS)-induced acute liver injury (ALI) via the Toll-like receptor 4 (TLR4) signaling pathway in the Raw264.7 cell line and in Balb/c mice. Methods: This study established an inflammatory cellular model and induced an ALI animal model. TLR4 was overexpressed by lentivirus and downregulated by small interfering RNA (siRNA) technology. The mRNA and protein levels of TLR4 and downstream molecules were detected in cells and liver tissue. The tumor necrosis factor-α (TNF-α) and interleukin (IL)-6 levels in supernatant and serum were determined by ELISA. The distribution and expression of mannose receptor C type 1 (CD206) and arginase 1 (ARG1) in the liver were tested by immunofluorescence. Mouse liver function and histopathological observations were assessed. Results: Administration of emodin reduced the protein and/or mRNA levels of TLR4 and its downstream molecules following LPS challenge in Raw264.7 cells and in an animal model. Additionally, emodin suppressed the expression of TNF-α and IL-6 in cell culture supernatant and serum. The inhibitory effect of emodin was also confirmed in RAW264.7 cells, in which TLR4 was overexpressed or knocked down. Additionally, ARG1 and CD206 were elevated in the emodin groups. Emodin also decreased serum ALT and AST levels and alleviated the liver histopathological damage induced by LPS. Conclusion: Emodin showed excellent hepatoprotective effects against LPS-induced ALI, possibly by inhibiting TLR4 signaling pathways.